Is the aerobic power a delimitating factor for performance on canoe slalom? An analysis of Olympic Slovak canoe slalom medalists and non-Olympics since Beijing 2008 to Rio 2016 - Bielik, V.; Dalcheco Messias, L. H.; Vajda, M.; Lopata, P.; Chudý, J.; de Barros Manchado-Gobatto, F. (Journal of Human Sport & Exercise, 2019)
Information regarding the aerobic power on canoe slalom performance is scares. Moreover, the comparison of maximum oxygen uptake (VO2max) via specific and non-specific ergometer for slalom kayakers may improve training prescription and controlling over Olympic cycles. Lastly, it is still unknown to what extent the VO2max delimitate the high performance in this sport. To test this perspective, a highly qualified sample is desired. In overall statistics, Slovakian athletes gathered 14 Olympic medals over the last sixteen years. Therefore, the main aim of this study is to compare the aerobic power of Olympic medallists and Non-Olympic Slovakian kayakers via specific and non-specific evaluations from Beijing 2008 to Rio 2016 Summer Olympic Games. Forty-two male canoe slalom athletes from Slovak national team were evaluated between the years 2006 and 2016. Slovakian athletes were tested for specific (i.e. paddling ergometer) and non-specific (i.e. treadmill) incremental protocols for VO2max determination. Over the last three Summer Olympic Games, the VO2max of Slovakian Olympic medallists was consistently lower than most of the Slovakian team. Moreover, disregarding the medallist characteristic or the moment, Slovakian kayakers presented higher VO2max on treadmill (57.7±6.8 mL/kg.min) when compared to paddle ergometer (46.9±6.5 mL/kg.min) (p=0.000; ES=1.6). Based on the collected data over the last ten years, we suggest that although aerobic power may play a relevant and indirect role on performance of slalom kayakers, does not delimitate the high performance in this sport.